Mitigating factors of screen time on children: a systematic review - Sharma, Harshita; Ahuja, Sona (International Journal of Contemporary Pediatrics, 2024)
Screen time is a modern dilemma that has unplugged children from Mother Nature. It is a time that the child spends using technologically driven devices such as television, smartphones, computers, gaming consoles, etc. For children, this shift is profound as they grow up in an immersed digital era that has lasting effects on their development and well-being. This systematic review aims to identify the intervention strategies for lessening screen exposure and finding mitigating factors of screen time for young children aged 4 to 12 years old. Screen time-related studies were searched in two databases PubMed and EMBASE. The keywords of “screen time”, “television”, “video”, “computer”, “mobile device”, “children”, “interventions”, and “strategies” used for search. The inclusion criteria are limited to specific study populations, intervention, comparison, and outcomes (PICOs), language, and published study types. The quality of articles was assessed using the Cochrane Risk of Bias (RoB) tool. Two researchers independently screened the literature and extracted the data. Seven eligible studies were included out of a total of four hundred and eighteen studies. The study sample ranges in the age range of (4-12 years) and the size ranges from (75 children and 39 parents to 709 children and 64 parents) participants. In included studies (randomized controlled trials), we found seven mitigating factors of screen time usage. It showed that in addition to educating people about the dangers of excessive screen time, effective programs, implementing restrictive practices, and providing a healthy home environment were the most common strategies used by the researchers. Future screen time reduction studies could benefit from incorporating more emphasis on implementing interventions like structured screen time, school involvement, health education, and more awareness programs to mitigate screen time among children.